Transformasi Balanced Scorecard di Era AI: Integrasi Cybersecurity dan Digital Sustainability untuk Ketangguhan UMKM - Diana Putri; Slamet Slamet (Universitas Multi Data Palembang, 2026)
The transition to Industry 5.0 necessitates AI adoption among Small and Medium Enterprises (SMEs), yet introduces critical vulnerabilities in cybersecurity and digital sustainability. Traditional Balanced Scorecard (BSC) frameworks are increasingly inadequate due to their reliance on lagging financial indicators and strategic blindness toward intangible digital risks. This study reconstructs the BSC by integrating cybersecurity and digital environmental metrics to enhance organizational resilience. Employing a mixed-methods approach comprising a Systematic Literature Review, Delphi technique, and comparative case studies the research formulates an